Tibial plateau leveling osteotomy in a 2 year old Newfoundland - Toscano, Matthew (2013)
A 2 year old castrated male Newfoundland, was presented to the Orthopedic Surgery Service to be admitted for a left stifle tibial plateau leveling osteotomy (TPLO). At home his owners were adhering to physical therapy guidelines for his right pelvic limb and reported that he was bearing minimal weight on his left pelvic limb. He was on a weight loss diet and he achieved his ideal weight. No other health issues were reported. His orthopedic exam revealed shifting hind limb lameness and severe hind limb muscle atrophy. In both stifles, medical buttress, crepitation and effusion with a positive cranial drawer and cranial tibial thrust were present. Radiographs revealed bilateral joint effusion with concurrent compression of the infrapatellar fat pad and periarticular osteophytes. Based on his radiographic findings and orthopedic examination cranial cruciate disease was diagnosed. Exploration of the right stift joint revealed an incompetent partial cranial cruciate ligament tear and an intact medial meniscus. A right TPLO was performed without complication. Ten weeks later, the osteotomy was determined to be radiographically healed and he was admitted into the hospital to have a left TPLO. His left cranial cruciate ligament also had an incompetent partial tear with an intact medial meniscus. This presentation will review stifle anatomy, orthopedic and radiographic assessment of the stifle, cranial cruciate disease and the planning and execution of a Tibial Plateau Leveling Osteotomy.